Teachers' shoe selection factors for school - Alias, Ayuni Nabilah; Yaakub, Norwahida (Malaysian Association of Consumer and Family Economics (MACFEA), 2023)
The selection of shoes among school teachers can significantly impact their musculoskeletal health when they are required to stand for prolonged periods in the classroom. Properly selected and supportive footwear can reduce the risk of developing or worsening MSDs, ensuring that teachers can perform their duties comfortably and effectively. This study dives into the interesting realm of school teacher shoe choosing, investigating the variables driving their decisions and putting insight into the broad range of shoe selections present in the classroom, from comfort to professionalism to personal expression. This cross-sectional study consisted of 212 school teachers from selected elementary school in Terengganu. Teachers were recruited through purposive sampling from the sampling frame that consisted of a list name of all teachers obtained from respective elementary schools’ administrative office. These teachers completed of all the surveys at their workplace, which was their respective schools. Results were analysed using descriptive analysis, which showed that in terms of shoe type selection, the preference for heels (50.5) edged out the desire for flats (49.5) among teachers. In terms of shoe size, the majority of teachers (38.2) wore size 5 shoes, followed by size 8 (21.2), size 6 (20.8), and size 7 (19.8). Furthermore, nearly half of the teachers (49) owned only one pair of shoes that they wore during school hours, and the majority (58.0) indicated an average shoe spending range of RM50 to RM100. Co-workers had the greatest influence on shoe selection when making a purchase, accounting for 36.8 of the total. With 32.1, advertising was the second most influential element. With percentages of 14.6, 11.8, and 14.7, respectively, salespeople, friends, and relatives influenced their shoe choices for school hours. This study has shed light on the numerous elements that influence shoe choosing among school teachers. Understanding these elements is critical for researcher as well as the footwear industry to promote proper shoe to be worn during school hours.